Innovative Methods of Teaching Mathematics in Education - Mansurbek Yangibaevich Gayipov (Euro Asian Journal Publishing, 2023)
The article is devoted to the targeted use of modern information technology tools, in particular, to solve problems in MS Excel in order to further increase the independent work in mathemetics
Keywords: ndependent work; information technology; software; determinant